Study of photonic crystals for novel lasers and photonics applications - Ooi, Raymond Chong Heng. (2008)
In this thesis, the fundamental physical effects of photonic crystals (PC) on the propagation of waves are studied, completely based on the macroscopic Maxwell's equations. We justify the valid usage of concepts used in the calculation of electronic band structures (EBS) for the computation of photonic band structures (PBS). We develop the fundamental theoretical frameworks for 1-D, 2-D and 3-D infinite photonic crystals composed of non-absorptive, non-dispersive, linear and isotropic materials. Powerful MATLAB programs are written to compute the photonic band structures, the EM fields and fields intensity distributions, the phase and group velocities and the effective refractive index of the 2-D photonic crystals in little time with remarkable precision using a personal computer.